The assessment of specific physical fitness of children aged 8 and 9 years participating in tennis classes using the Jindrich Hoehm test - Szpala Agnieszka; Rutkowska-Kucharska Alicja; Syrewicz Paweł (Sciendo, 2014)
Study aim: The purpose of the study was to use the Jindrich Hoehm test to evaluate physical fitness in boys and girls aged 8 and 9 years participating in tennis classes.